The 2021 field season at Kalba: Results of the excavations and geoarchaeological surveys - Schwall, Christoph; Brandl, Michael; Börner, Mario; Lindauer, Susanne; Deckers, Katleen; Riehl, Simone; Cramer, Anja; Hauzenberger, Christoph; Yousif, Eisa; Jasim, Sabah A. (Proceedings of the Seminar for Arabian Studies, 2023)
The ongoing fieldwork at Kalba (K4) at the Gulf of Oman focused on the area outside the Early Bronze Age ditch construction and its subsequent use in the later Bronze Age and Iron Age periods. Our previous investigations have exposed a mud-brick wall section in the lower eastern profile of the trench whose function and specific dating was unclear. The excavated superimposed architectural remains in this area indicate that approximately the same spatial dimensions of the sites’ central part was continuously enclosed. Besides environmental studies (archaeobotanics, marine reservoir effect) and radiocarbon data, the archaeological material discovered during the investigations extend our knowledge about craft activities on site. Apart from metallurgy and stone knapping, a fragment of a semi-finished softstone vessel attests local manufacturing of specialised craft products. For this reason, the geoarchaeological survey was extended based on the artefacts found at Kalba. The variety of lithic materials used to produce various objects demonstrates the deliberate choice of particular stone types, and the awareness of the site’s inhabitants of local rock deposits. In this context, it is worth considering whether specific rock materials were procured as trading goods by the prehistoric coastal community.